How I learned geography - Shulevitz, Uri, 1935- (New York : Farrar Straus Giroux, 2008)
As he spends hours studying his father's world map, a young boy escapes the hunger and misery of refugee life. 'Based on the author's childhood in Kazakhstan, where he lived as a Polish refugee during World War II.
Caldecott Medal/Honor.
School Library Journal starred.
Wilson's Children.
Book Links (A.L.A.), January 2009.
Book Links-starred, July 2008.
Booklist starred, May 2008.
Keywords: Shulevitz, Uri, -- 1935- -- Childhood and youth -- Juvenile fiction; Shulevitz, Uri, -- 1935- -- Fiction; Shulevitz, Uri, -- 1935- -- Fiction; Geography -- Juvenile fiction; Maps -- Juvenile fiction; Refugees -- Juvenile fiction; Geography -- Fiction; Maps -- Fiction; Refugees -- Fiction; Geography -- Fiction; Maps -- Fiction; Refugees -- Fiction